Histological analysis of the use of biphasic ceramics based on hydroxyapatite and β-tricalcium phosphate in maxillary sinus floor elevation surgery: pilot study - Padovan, Luis Eduardo Marques; Garcia E Sousa, Diego; Padovan, Silvia Helena Marques; Lopes De Oliveira, Guilherme José Pimentel; Silva, Ricarda Duarte Da; Claudino, Marcela (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractObjectiveTo evaluate the bone repair associated with the use of biphasic ceramics based on hydroxyapatite and β-tricalcium phosphate (HA/TCP) in the procedures of maxillary sinus membrane elevation in human beings.Material and methodTen patients with a residual bone ridge in the posterior maxillary region between 3 mm and 5 mm in height were selected and indicated for procedures of bone grafting associated with maxillary sinus lift procedure. The maxillary sinuses were filled with HA/TCP, and after 8 months, the implants were implanted and a bone biopsy was collected with the aid of a trephine drill, which was then submitted to histological analysis for the evaluation of the composition of the grafted area.ResultThe histological description analysis of the biopsies revealed the presence of vital and immature bone tissue, juxtaposed to the biomaterial. Histomorphometric analysis showed that the biopsy composition was in average 28.8%, 27.4%, and 43.6% of bone tissue, biomaterial, and soft tissue, respectively.ConclusionThe areas grafted with HA/TCP presented the adequate amount of bone formation that allowed the implantation of the implants. The success of the grafting procedure with this biomaterial was associated with its osteoconduction potential that allowed the formation of bone tissue in close contact with HA/TCP.

ResumoObjetivoAvaliar o reparo ósseo associado ao uso da cerâmica bifásica a base de hidroxiapatita e β-tricálcio fosfato (HA/TCP) nos procedimentos de elevação da membrana do seio maxilar em humanos.Material e métodoForam selecionados 10 pacientes com rebordo ósseo residual entre 3 mm e 5 mm de altura na região posterior da maxila e que tinham indicação para procedimentos de enxertia óssea associado ao levantamento de seio maxilar. Os seios maxilares foram preenchidos com HA/TCP, e após 8 meses, foi executado a instalação dos implantes e nesse momento foi realizada a coleta de um fragmento ósseo com auxílio de uma broca trefina, o qual foi submetido à análise histológica da área enxertada.ResultadoA análise histológica das biópsias revelou a presença de tecido ósseo vital e imaturo, justaposto ao biomaterial. A análise histomorfométrica revelou percentuais de 28,8%, 27,4% e 43,6% para tecido ósseo, biomaterial e tecido mole, respectivamente.ConclusãoAs áreas enxertadas com a HA/TCP apresentaram quantidade adequada de formação óssea que permitiu a instalação dos implantes. O sucesso do procedimento de enxertia com esse biomaterial esteve associado ao seu potencial de osteocondução que permitiu a formação de tecido ósseo em íntimo contato com a HA/TCP.
Análise histológica do uso da cerâmica bifásica a base de hidroxiapatita e β-tricálcio fosfato em cirurgia de elevação de assoalho de seio maxilar: estudo piloto
Keywords: Maxillary sinus; bone transplantation; dental implants; Seio maxilar; transplante ósseo; implantes dentários